The Effects of Diet Containing Fish Oil on Some Blood Parameters and the Performance Values of Broilers and Cost Efficiency - Alparslan, G.; Ozdogan, M. (International Journal of Poultry Science, 2006)
This study aimed to investigate the effects of feed containing no fish oil and feed containing 2 % and 4 % fish oil on the performance and some blood parameters of broilers. It was found that the differences among the groups were significant regarding the performance values. It was found that high-density lipoproteins HDL in blood parameters of females, Aspartate aminotransferase AST in males were higher in the group including 4 % fish oil compared to the group control (p< 0.01). The highest gross margin in the treatment groups was observed in the group 2% FO and then the group C fallowed this group.